2013
DOI: 10.1155/2013/456375
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Thermal Cavitation Problem of a Preexisting Microvoid in a Viscoelastic Sphere

Abstract: The cavitation problem of a preexisting microvoid in the incompressible viscoelastic sphere subjected to the uniform temperature field was studied in this paper. Based on the finite logarithmic strain measure for geometrically large deformation, the nonlinear mathematical model of this problem was established by employing the Kelvin-Voigt differential type constitutive equation of thermoviscoelasticity. Adopting the dimensionless transformation of each parameter, growth curves of the microvoid radius increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Cristiano et al [22] and Hamdi et al [23] have recently conducted further experiments in order to understand the connection between cavitation and material fracture. Dorfmann and Burtscher [24] and Kumar et al [25] suggested that cavitation was the primary cause of irreversible stress softening in seismic bearings; the same opinion was expressed for metal materials [26][27][28]. Increased attention has also been paid to cavitation associated with general geometries and loading conditions, and its numerical computations [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Cristiano et al [22] and Hamdi et al [23] have recently conducted further experiments in order to understand the connection between cavitation and material fracture. Dorfmann and Burtscher [24] and Kumar et al [25] suggested that cavitation was the primary cause of irreversible stress softening in seismic bearings; the same opinion was expressed for metal materials [26][27][28]. Increased attention has also been paid to cavitation associated with general geometries and loading conditions, and its numerical computations [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%